'Globalizing' academics? Ranking and appropriation in the transformations of the world-system. Issue 1 (2nd January 2020) - Welsh, John
ABSTRACT: In an historical materialist analysis, the article challenges the dominant understanding of global academic rankings as 'inevitable' and 'here to stay'. Instead, rankings are treated as historically transformative 'tracings' over the accumulation of capital in the world-system, and thus offer a contingent strategic response to three historical shifts in global political economy: 'financialization', displacement of the Core, and an shift to surplus 'appropriation' in the core. By understanding these transformative shifts as elements of an historic 'inversion' of the global frontier of capitalization, the argument: (1) connects global rankings to neoliberal capitalism; (2) challenges the utopian view of rankings as instruments of marketization; and most specifically (3) opens up a space between frontiers of appropriation and commodification proper, indicating how rankings exist in a historically transient and politically dialectical space of hybrid outcomes, imperfect commodifications, and indirect subjections, that are bound to the contradictions of accumulation in contemporary world history.